2017
DOI: 10.5812/ijcm.6260
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival of Glioblastoma Multiform (GBM) in Iranian Patients

Abstract: Background: Glioblastoma Multiform has been a common and fatal brain tumor. In this regard, there was ambiguity around patient survival rates in Iran que to data insufficiency. In this study, we have analyzed the overall and progression free survival in GBM patients at Milad Tehran hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Correlating the available clincopathological features including the survival data of GBM cases with the gene expression results revealed that poor overall survival and disease-free survival were found significantly among patients as reported by previous studies [ 44 , 45 ]. Despite that GBM can occur in individuals of any age according to the previous population-based studies, the median age is nearly above 60 years.…”
Section: Discussionsupporting
confidence: 75%
“…Correlating the available clincopathological features including the survival data of GBM cases with the gene expression results revealed that poor overall survival and disease-free survival were found significantly among patients as reported by previous studies [ 44 , 45 ]. Despite that GBM can occur in individuals of any age according to the previous population-based studies, the median age is nearly above 60 years.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, good perioperative physical and neurological conditions of iGBM patients contribute to tolerance to general anesthesia and complete chemoradiation therapy. As a result, the median PFS and OS of iGBM patients (11.5 and 20.0 months, respectively) were better than previous reports (6.3-7.1 months and 10.1-15.2 months) [9,10,13,15,27]. It is worth noting that the general patient demographics and molecular features of iGBM were not different from those of general GBM.…”
Section: Discussionmentioning
confidence: 55%
“…Even with the best treatment with maximal safe surgical resection following chemoradiotherapy with temozolomide, the median overall survival of GBM patients does not reach two years [7]. The representative prognostic factors of GBM patients include age, Karnofsky performance score (KPS), molecular diagnosis including isocitrate dehydrogenase 1 and 2 (IDH1/2) mutations and O-6methylguanine deoxyribonucleic acid methyltransferase (MGMT) promoter methylation status, and the extent of initial surgical resection [8][9][10][11][12][13][14]. Additionally, a small preoperative contrast-enhanced tumor on imaging is an independent favorable prognostic factor [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identi ed that other than a tumor located in the periventricular zone, the risk factors for LMD are long survival [9], young age [7,9], larger initial tumor size [7],and MGMTpromoter methylation [6].Patients with ITDhave a longerOS (19.7 months) than the general GBM population (10.1-15.2 months) [25][26][27][28][29].By contrast, the median age of the patients(66.0 years)is consistent with that of the patients with GBM (63-65 years) [27,[30][31][32].Moreover, the MGMTpromoter'slow methylation status (21.4%) in the patients was lower than that in the general GBM population (45%) [33]. and the extent of resection (total resection 28.6%) did not exceed previous reports (20-43%){Chang, 2005 #13} [30,34].…”
Section: Discussionmentioning
confidence: 99%